2018
DOI: 10.1002/hep.29887
|View full text |Cite
|
Sign up to set email alerts
|

The high burden of alcoholic cirrhosis in privately insured persons in the United States

Abstract: In a nationally representative cohort of privately insured persons, AC enrollees were disproportionately sicker at presentation, were admitted and readmitted more often, and incurred nearly double the per-person health care costs compared to those with non-AC. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 38 publications
5
164
0
Order By: Relevance
“…Cirrhotic and noncirrhotic ALD prevalence has been estimated at approximately 2% in the general US population, whereas AC in the US Veterans' population was estimated at 327 per 100,000 enrollees . In privately insured US patients, AC has been estimated at approximately 100 per 100,000 enrollees, and, overall, rates are projected to rise over time . Worldwide, AC deaths account for about 10% of all alcohol‐attributable deaths, and nearly half of those deaths are due to liver disease, resulting in the loss of 22.2 million disability‐adjusted life years annually .…”
Section: Prevalence and Burden Of Alcohol‐associated Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Cirrhotic and noncirrhotic ALD prevalence has been estimated at approximately 2% in the general US population, whereas AC in the US Veterans' population was estimated at 327 per 100,000 enrollees . In privately insured US patients, AC has been estimated at approximately 100 per 100,000 enrollees, and, overall, rates are projected to rise over time . Worldwide, AC deaths account for about 10% of all alcohol‐attributable deaths, and nearly half of those deaths are due to liver disease, resulting in the loss of 22.2 million disability‐adjusted life years annually .…”
Section: Prevalence and Burden Of Alcohol‐associated Liver Diseasementioning
confidence: 99%
“…In the United States, ALD competes with chronic HCV as the leading indication for liver transplantation (LT) . Medical costs are high for AC, driven in part by the higher number of admissions for these patients . In addition, deaths related to alcohol use are frequently underestimated due to the stigma of alcohol use and lack of candor in reporting .…”
Section: Prevalence and Burden Of Alcohol‐associated Liver Diseasementioning
confidence: 99%
“…Cirrhosis is common, affecting up to 5 million Americans, and its prevalence is increasing . It is characterized by poor quality of life and life‐limiting complications such as variceal hemorrhage, ascites, hepatic encephalopathy (HE), and hepatocellular carcinoma (HCC) . There are standard measures that can be undertaken to forestall many of these complications and improve patient outcomes.…”
mentioning
confidence: 99%
“…First, there is potential for inaccurate coding that could lead to misclassification bias of CLD status, measurement bias for covariates of interest, and ascertainment bias for clinical outcomes. However, prior studies using our coding algorithm for CLD status has demonstrated good sensitivity and specificity and a positive predictive value of 80% or greater . In addition, while we attempted to reduce confounding of opiate use due to surgery by removing patients with anaesthesia codes, the outpatient pharmacy file does not provide context for the indication of opiate use.…”
Section: Discussionmentioning
confidence: 99%